Instant karma - Meyer, Marissa (Feiwel and Friends, 2020)
Prudence Daniels is a chronic overachiever and is always quick to cast judgment on those she deems lazy or rude. After a night out with her friends, she wakes up with the ability to cast instant karma on those around her. Pru punishes everyone from vandals to gossips, but there's one person on whom her powers don't work: Quint Erickson, her slacker lab partner. When Pru reluctantly begins working at Quint's family's marine rescue center, she learns not just about otters and environmental upheaval, but how thin the line is between generosity and greed and love and hate.